(untitled) (Eureka Journal of Physical and Chemical Research, 2026)
The base of the ion implantation method has been studied, where the energy of ions can vary from several hundred electron volts to gigaelectron volts. It has been shown that ion bombardment allows for the modification of almost all properties of the near-surface region of a solid, resulting in the formation of homogeneous, continuous films. These processes are carried out in ultra-high vacuum conditions (P ≤ 10−8 Pa). Low-energy ions implanted at shallow depths create surface defects at the early stage of epitaxial film growth, which later act as centers of crystal nucleation.